The extra-thyroidal distribution of sodium iodide symporter - Gadisi, Rinae Prisca; Naicker, Meleshni; Naidoo, Strinivasen (Frontiers in Endocrinology, 2025)
The intrinsic transmembrane protein known as sodium iodide symporter (NIS) facilitates the active transport of iodide across the basolateral membrane of thyroid follicular cells. Iodine is an essential molecule that is used to produce the classical thyroid hormones that contribute to growth and development of various parts of the body and play a significant role as metabolic regulators. The cloning of the human NIS gene in 1996 has led to widespread advancements in thyroid-related research. Amongst these, the significant discovery of extra-thyroidal expression of thyroid-specific genes and proteins such as NIS in both human and non-human subjects has been well documented. The identification of NIS protein in non-thyroid tissue provides potential targets for therapeutic interventions aimed at modulating autoimmune responses in various parts of the body. In the diagnosis and prognosis of different types of cancer, the molecular and protein expression of NIS may prove to be an important cancer biomarker. This review will cover the extra-thyroidal distribution of NIS, as well as its pathophysiological implications in various tissues of human and non-human organs.